DECENTRALISATION, INCLUSIVE DEVELOPMENT AND GOOD GOVERNANCE (World Bulletin of Social Sciences, 2021)
The democratic governance, decentralisation and inclusive development have organic links. The Panchayati Raj Institutions (PRI) has a decisive role to play in reducing poverty in rural areas and this can be possible through a decentralised democratic governance structure. These institutions must be self-sufficient and should be successful, effective in the delivery of services. People’s involvement in the process of governance of these PRIs is vital not only for democracy but also to have inclusive development. But sustained participation of the people, particularly of the marginalised is the biggest challenge before democracy, particularly for a democratic system that functions in an environment of inequalities and oppression in rural areas. Representative democracy has not been able to address the questions of poverty, inequalities and of development in rural areas. As this is a centralised system it has a limited reach in terms of participation of the common people in rural areas. Democratic participation and practice are much beyond the notions of voting, electoral competitiveness. The spirit of PRIs is to create and sustain democratic space for the masses at the grass roots level so that both democracy and development will be inclusive and decentralised. But this has not happened so far substantially. But there are immense possibilities for this in the PRIs. But the practice is altogether different. This paper is a theoretical study on the problem of interrelationship of Inclusive Development, Decentralised Democracy and Good Governance. It argues that Neo-liberalism is in contradictions with democracy and inclusive development